Effects of Poppy Seed Cake on Physicochemical, Textural, and Microbiological Properties of Cheese Chips - Albay, Z; Gün, NS; Şimşek, B (Journal of the Hellenic Veterinary Medical Society, 2025)
The purpose of this study was to look into the effects of adding poppy seed cake at various rates (1% and 3%) to cheese chips on their physicochemical properties, color, texture, elemental, and microbiological qualities. The findings revealed that poppy seed cake raised pH, dry matter, protein, and ash levels while decreased fat and salt content (p<0.05). The addition of poppy seed cake reduced the brightness and yellowness of chips while increasing their redness (p<0.05). It also made chips less hard and more fragile. Elemental analysis found that poppy seed cake increased calcium, potassium, magnesium, sodium, phosphorus, and zinc levels. poppy seed cake significantly increased lactobacilli levels (p<0.05) and decreased TMAB (p<0.05), while also reducing Bifidobacterium animalis subsp. lactis BB-12 (p<0.05) and slightly increasing Lactobacillus acidophilus LA-5. Additionally, poppy seed cake was determined to improve probiotic survival as well as general microbiological quality. These findings suggest that poppy seed cake could improve the quality and nutritional content of chips. Adding 3% poppy seed cake resulted in the most significant increases in dry matter, protein, and essential minerals like calcium, potassium, magnesium, and phosphorus. The amount of total mesophilic aerobic bacterias was significantly reduced, while the number of beneficial lactobacilli increased. It also provided the ideal balance of texture and microbiological qualities for the chips. As a result, it is believed that using 3% poppy seed cake will improve the overall quality of cheese chips.